(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Education has invaluable role in the promotion of sustainable development. Its important task is to promote the formation of understanding the environmental and development issues of every person. It is a necessity to achieve the change of orientation of personal values and to develop their abilities to solve the issues concerning sustainable development. One of the subjects that can help to perform the task is ecology. Ecology is a subject that could promote the understanding between human being and environment and to create the positive attitude towards the nature. Tendencies of ecological education in Latvia are recovered in the report. For recovering the tendencies research was done which involved summarizing the results about pupils real knowledge, skills in the sphere of ecology and motivation to study ecology.